RELATIONSHIP BETWEEN BLUE OCEAN STRATEGY, CUSTOMER BEHAVIOR, AND ISLAMIC BANK PEFORMANCE - nasfi nasfi (Jurnal Ipteks Terapan, 2020)
There have been many studies conducted to determine the effect of differentiation strategies in business. Even so, there is still little empirical research that focuses on the impact of the blue ocean strategy on customer behavior in the financial services industry, especially banking. This study evaluates the effect of the blue ocean strategy on customer behavior and how it impacts on bank performance. Two hundred eighty-two customers from 20 Islamic commercial banks and Islamic business units filled out an online questionnaire. Overall, we found that the blue ocean strategy had a positive effect on advocacy behavior and customer loyalty. In addition, we find that advocacy does not have a significant effect on perceptions of bank performance, while loyalty has a significant positive effect on perceptions of bank performance. This result has implications for the importance of further research on the effects of the blue ocean strategy and the importance of sharia banking adopting this strategy consciously and systematically to increase customer loyalty and bank performance.